2021
DOI: 10.1002/jsfa.11265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sesame, canola and sesame‐canola oils on body weight and composition in adults with type 2 diabetes mellitus: a randomized, triple‐blind, cross‐over clinical trial

Abstract: BACKGROUND: Recent investigations have proposed that sesame and canola oils might affect body fat distribution. The present study aimed to examine the effects of sesame, canola and sesame-canola (a blend of sesame and canola oils) oils on body weight and composition in adults with type 2 diabetes mellitus in the context of a randomized, triple-blind, three-way, cross-over clinical trial.RESULTS: Eligible participants were randomized to replace their regular dietary oil with sesame oil (SO), canola oil (CO) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…However, no significant differences in these indicators were observed between the two groups. In support of our results, in a well-designed study conducting by Raeisi et al, which assessed the effect of SO consumption for 9 weeks in adults, no change in body weight and BMI were observed [53]. Also, Yazdi et al showed similar results [54].…”
Section: Anthropometric Indicessupporting
confidence: 90%
“…However, no significant differences in these indicators were observed between the two groups. In support of our results, in a well-designed study conducting by Raeisi et al, which assessed the effect of SO consumption for 9 weeks in adults, no change in body weight and BMI were observed [53]. Also, Yazdi et al showed similar results [54].…”
Section: Anthropometric Indicessupporting
confidence: 90%
“…Furthermore, in hypertensive individuals, overall effects on blood pressure were inconsistent. Despite the methodological weaknesses noted, trials administering sesame oil showed evidence of a trend toward correcting aberrant blood glucose and hemoglobin A 1c levels in subjects with diabetes and metabolic syndrome 76–79,87 . When markers of inflammation were measured in 3 studies, 69,70,87 there was no consistent influence of sesame oil consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the methodological weaknesses noted, trials administering sesame oil showed evidence of a trend toward correcting aberrant blood glucose and hemoglobin A 1c levels in subjects with diabetes and metabolic syndrome. [76][77][78][79]87 When markers of inflammation were measured in 3 studies, 69,70,87 there was no consistent influence of sesame oil consumption. In addition, in those trials that evaluated the impact of ingestion of sesame extracts on anthropometric measures, no consistent effect was reported.…”
Section: Potential Health Benefits Of Sesame In Human Trialsmentioning
confidence: 98%
“…Moreover, sesame samples varied considerably in the form and manner that they were administered to participants. Specifically, sesame was provided as unground seeds, 61,90 seed powder, 48,60,66,68,74,86,88 oil incorporated into vegetable soup, 70 oil dispensed to individuals for inclusion in foods, 77 oil dispensed individually to patients for exclusive use as cooking oil, 80 bulk quantities of oil provided to households for use as the only edible oil in food preparation and cooking, 69,71,75,76,78,79 and sesame-containing food bars. 61 These differences in treatment methods are important to acknowledge, because they may alter the bioavailability of bioactives present in sesame products.…”
Section: Potential Health Benefits Of Sesame In Human Trialsmentioning
confidence: 99%